MODERN BUSINESS EDUCATION PROBLEMS AND CHALLENGES (Economics and region, 2017)
UDC 377.3 “312”Riashchenko Viktoriia, Dr.oec., prof. Koryuhina Catherine, Mg.oec., Mg.Phil. Assist.Prof. ISMA University. Modern Business Education Problems and Challenges. Nowadays, the public significance of the education (both general and professional) has increased tremendously. Global changes in the technological, economic and social development of world civilization have turned education into a strategic factor in the progress of society. The growth of the scientific, technical, socio-cultural and spiritual potential of the society is directly related to the level and condition of the education system, the raising of the educational and professional level of the population. The influence of a post-industrial society formation on education should also be noted. The main question is: what kind of social order will replace the industrial system, and the answer to it becomes even more urgent. In the post-industrial society has the background of machine technology, information technology, based on the increased intellectual potential, is becoming increasingly important. This phenomenon must be accompanied by an appropriate modernization of the educational system. If education can not provide support for career changes, then education as an independent category of business can leave the market.Keywords: development, business education, process of education, education.